Analisis Implementasi Program Gerakan Arah Kiblat 1000 Masjid/ Mushola di Kabupaten Sleman - Muthmainnah Muthmainnah; Zainul Arifin; Toto Hermawan; Barid Barid; Akhmad Muhaini (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2019)
This qualitative case study research deals with the implementation of the 100 Mosques / Musalla movement which socializes the MUI fatwa number 5 of 2010 concerning the Direction of the Qibla in Sleman Regency. by taking two districts to represent the conditions of urban and rural communities. The data collection methods are involved observation, documentation and interviews with 10 informants from community leaders in the two regions. Some people reject change because of their belief in the myth of the ijtihad of their predecessors, besides considering technology not as a means to perfect worship, including measuring the direction of the Qibla. However, most of the changes due to the certification of the mosque's Qibla direction do not require changes to the building, but only adjusting the prayer lines (saff) in the mosque. The dissemination of astronomical technology, which is understood as a form of ijtihad, can be done so that changes and developments that occur in the direction of the mosque's qibla can be accepted by the community.